EARLY PALEOZOIC GRANITOIDS IN THE EASTERN MARGIN OF THE ARGUN' TERRANE, AMUR AREA: FIRST GEOCHEMICAL AND GEOCHRONOLOGIC DATA - Sorokin A.A.; Kudryashov N.M.; Jinyi L.; Pin Y.; Guihua S.; Liming G.; Zhuravlev D.Z. (My University, 2004)
The leucocratic subalkaline granites found in the eastern margin of the Argun' terrane have an U-Pb age of 467-472 Ma and compose relatively small tectonic blocks among Silurian and Devonian terrigenous-carbonate deposits and Late Paleozoic granitoids. According to the first geochemical data, the Early Paleozoic subalkaline leucogranites are similar to A-type granitoids of Whalen et al. (1987). The isotopic composition of the granitoids corresponds to that of Central Asian Caledonian and Riphean crustal provinces. The variable isotopic-geochemical characteristics of these rocks, for example, their eNd from +2.4 to -6.8 and TNd(DM-2st) from 1.0 to 1.2 Ga, suggest that the source of the melts was compositionally heterogeneous.
Keywords: Paleozoic; Paleozoic; Палеозой